Analysis of the thrust deduction in waterjet propulsion – The Froude number dependence. (15th March 2018) - Eslamdoost, Arash; Larsson, Lars; Bensow, Rickard
Abstract: The definition of thrust deduction in waterjet propulsion is different from that of a propeller driven hull and cannot be interpreted in the same way. A particularly interesting feature of the waterjet thrust deduction is the large variation with Froude number. This is well known from experience, but has never been fully explained. The objective of this paper is to use CFD to address the reasons for these large variations. To this end, the thrust deduction fraction is split into resistance increment fraction and jet thrust deduction fraction. The former is due to the self-propelled hull resistance change in comparison with the bare hull resistance and the latter is due to the difference between gross and net thrust. This split reveals that the main reason for the thrust deduction variation is the hull resistance change. Analysis of the resistance increment in different speed ranges is performed by studying the hydrostatic and hydrodynamic pressure changes on the hull as well as the friction change due to the waterjet system. Despite the negative thrust deduction fraction in the intermediate speed range there is no indication of a resistance reduction compared to that of the bare hull at these speeds. Highlights: The waterjet thrust deduction fraction, t, varies a lot in different speed ranges. t is split into resistance increment fraction and jet thrust deduction fraction. The main reason for the t variation is the hull resistance change. A negative t is not an indication of the hull resistance reduction. The major reason for the negative t is the jet system thrust deduction fraction.